63.3k views
4 votes
2m = 1 + m what do I need to do to solve this problem

User Fraggle
by
5.1k points

2 Answers

3 votes

The solution to this problem is m = 1.


In order to solve any algebraic equation, we must get the letter we are looking for by itself, so that the equation reads "m = [value]".


In this case, to get m by itself, we must first get all of the terms that include m on the same side so we can collect the like terms and simplify.


This means subtracting m from both sides of the equation, so we get:


2m = 1 + m

- m

m = 1


I hope this helps!

User Roam
by
5.2k points
4 votes

First you have to subtract the m on the right from the left so it would just end up being m = 1

Hope this helps

-Ayden

User Jimmy Baker
by
5.3k points